Estimation of Handgrip Strength and Its Correlations with Selected Functional and Anthropometric Variables in Patients with Rheumatoid Arthritis - Supriya Arora, Shyamal Koley (International Journal of Advanced Science and Technology, 2020)
Background: Rheumatoid arthritis is a chronic, systemic inflammatory disorder that primarily affects the small joints of hand. Thus, estimation of handgrip strength is essential , as it is reported that rheumatoid arthritis affects the strength and functions of hand of patients. Some anthropometric and functional variables have also been studied to observe the correlation of handgrip strength on them in patients with rheumatoid arthritis. Materials and methods: The study was conducted purposively selected 205 patients with rheumatoid arthritis from Christian Medical College and Hospital and Satguru Partap Singh Hospital, Ludhiana, Punjab, aged 25-65 years. The subjects were assessed for handgrip strength (both dominant and non-dominant), two functional variables, i.e. physical function and pain, and eleven anthropometric variables namely, height, weight, BMI, hand circumference, hand length, hand breadth, triceps skinfold, arm muscle area, arm area, arm fat area and arm fat index Results: It was observed that the patients with rheumatoid arthritis had significantly lesser (p<0.001) mean values of dominant and non-dominant handgrip strength than controls. It was also found that both younger and older patients had significantly lesser (p<0.001) mean values than their control counterparts. Both dominant and non-dominant handgrip strength of patients with rheumatoid arthritis showed significant positive correlations with height, hand circumference, hand length, hand breadth, triceps skinfold and arm muscle area, and significant negative correlations with physical function, arm fat area and arm fat index. Conclusion: It might be concluded that dominant and non-dominant handgrip strength had significant reduction in patients with rheumatoid arthritis as compared to controls. Both dominant and non-dominant handgrip strength had significant positive correlations with some anthropometric variables.